Respuesta :

Answer:

42

Step-by-step explanation:

a squared = b squared plus c squared

Answer:

The answer to your question is   b = 42

Step-by-step explanation:

Data

hypotenuse = 70

leg 1 = 56

Process

1.- To solve this problem use the Pythagorean theorem.

             c² = a² + b²

c = hypotenuse

a = 56

b = x

2.- Solve for b

              b² = c² - a²

3.- Substitution

              b² = 70² - 56²

4.- Simplification

               b² = 4900 - 3136

               b² = 1764

5.- Result

               b = 42